Ecological and Health Risks Assessment Due to Carbon Monoxide (CO) Exposure : Implications of Air Pollution for Parking Attendants - Tri Septian Maksum; Sarinah Basri K; Yolanda Talib; Kraichat Tantrakarnapa (International Journal of Hydrological and Environmental for Sustainability, 2023)
Carbon monoxide (CO) is the main pollutant from motor vehicle emissions which is dangerous if inhaled by humans. This study aims to analyze the ecological and health risks caused by carbon monoxide gas pollution to parking attendants on roads in Gorontalo City. This type of research is an observational study using the Ecological Risk Assessment (ERA) and Health Risk Assessment (HRA) approaches through field studies. The number of samples was 60 respondents and air samples were taken from 12 locations and each location consisted of 2 points. Data were analyzed descriptively through studies (ERA) and (HRA). The results showed that there were 8 locations that had CO concentrations that exceeded the threshold value. Thus the level of CO on roads in Gorontalo City is included in the unsafe category. Characterization of ecological risk due to CO exposure on roads in Gorontalo City is classified as dangerous for the environment where 4 locations are in the low hazard category (HQ 0.1-1.0) and 8 locations are in the medium hazard category (HQ 1.1-10). The highest real-time exposure CO intake was at the Jamu Solo Store location, namely 1.8501799100 mg/kg/day with an RQ value of 2.2291324200 (at risk), while the lowest was at the Extra Bakery location 0.0746788000 mg/kg/day with an RQ value of 0.0899744600 (no risk). It is recommended for parking attendants to wear masks while working and reduce smoking habits.